2004
DOI: 10.1016/j.ijindorg.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The competitive effects of mergers between asymmetric firms

Abstract: This paper evaluates both efficiency increasing and efficiency decreasing mergers in a procurement setting in which firms differ in the likelihood that they have high production costs. Profitable efficiency increasing mergers often decrease the expected price, but profitable efficiency decreasing mergers always increase it. For a particular pair of firms, there may be no profitable mergers. If there are, then the most profitable merger may decrease efficiency. Consequently, merging firms that are able to choos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Dalkir, Logan, and Masson (2000) and Tschantz, Crooke, and Froeb (2000) examine mergers in asymmetric¯rst-price auctions using simulated equilibrium bidding strategies. Thomas (1998) examines mergers in asymmetric¯rst-price auctions by deriving equilibrium bidding strategies for the binomial cost distribution. Brannman and Froeb (2000) and Froeb, Tschantz, and Crooke (1998) examine mergers in asymmetric second-price auctions with the extreme value cost distribution.…”
Section: The E®ects Of Mergers In Open Auction Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalkir, Logan, and Masson (2000) and Tschantz, Crooke, and Froeb (2000) examine mergers in asymmetric¯rst-price auctions using simulated equilibrium bidding strategies. Thomas (1998) examines mergers in asymmetric¯rst-price auctions by deriving equilibrium bidding strategies for the binomial cost distribution. Brannman and Froeb (2000) and Froeb, Tschantz, and Crooke (1998) examine mergers in asymmetric second-price auctions with the extreme value cost distribution.…”
Section: The E®ects Of Mergers In Open Auction Marketsmentioning
confidence: 99%
“…Starting from each initial pro¯le, we exhaust all possible pro¯table mergers to arrive at the stable pro¯les. 33 For Table 1, we assume that F is uniform over the unit interval, that 32 Using a models that are mathematically similar, Thomas (1998) and McAfee (1994) also¯nd that in some cases there is no incentive for merger to monopoly. These results from the auction models are clearly at variance with the symmetric or asymmetric Nash-Cournot models.…”
Section: Qedmentioning
confidence: 99%
“…The first condition is relatedness and complementarity ( Yu et al, 2015 ; Wang and Zajac, 2007 ). Thomas (2004) found that integration costs are lower if both firms run similar operations, because they can better optimize and join together complementary resources for value creation, findings that were later supported by the work of Wang and Zajac (2007) . Drawing on this work, we assume that horizontal mergers in the same industry involving both relatedness and complementarity should generate positive value in the form of lower costs, although in combination with the other conditions that follow here.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Faulli-Oller (2002) analyzes such mergers and finds that merger profitability increases when the initial cost difference between the merging firms is larger, because after the merger all output is produced using the lowest cost technology. Thomas (2004) analyzes mergers between asymmetric firms in a procurement setting, and finds that the identity of the merging firms, and the effect of the merger on costs, determine whether the merger is profitable or not, and whether it increases or decreases the final price. Cost asymmetries affect the profitability of mergers as well as the profitability of R&D cooperation.…”
Section: Introductionmentioning
confidence: 99%